Effects of preference on performing a self-care skill among children with autism spectrum disorder. Issue 2 (3rd April 2019) - Duhanyan, Kimberly; Harper, Jill M.; Heal, Nicole; Luiselli, James K.
Abstract: In this study, four children with autism were assessed to determine their preference choices for toothbrushes and toothpastes included during self-care skills teaching sessions. For two of the children, the presence of high-preference (HP) materials was associated with improved independent tooth brushing when compared to the presence of low-preference (LP) materials. There was no difference in independent tooth brushing between HP/LP conditions for the other two children. These findings suggest that preference and choice of materials alone can be a helpful instructional strategy for care providers serving children who have neurodevelopmental disorders and skill deficits.